Profile of Student’s Mathematical Connection Abilities Based on Mathematical Learning Style and Personality Type - Sutihat Sutihat; Heni Pujiastuti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
Mathematical connection ability is a person's ability to connect every concept or material in mathematics with other disciplines and with everyday life. The ability of one's mathematical connection varies from person to person, this is due to mathematical learning styles and different personality types. This study aims to find out: Profile of students' mathematical connection abilities based on mathematical learning styles and personality types. The subjects of this study were students of class XI IPA 1 and XI IPA 2 at SMAN 19 Tangerang Regency. The type of research used is qualitative research. From this study, it can be concluded that: 1) Mastery Learning students work in stages, but are constrained by non-routine questions. Interpersonal Learning students work structurally but are constrained by non-routine questions. Understanding Learning students are constrained by problems that are not routine because they have not been able to understand the concept properly. Self-Expressive Learning students complete the connection problem using their creative ideas. 2) Guardian students can solve the connection problem because they have strong memories so they are able to remember the concepts that have been learned. Artisan students work on the problem in a hurry so that the results obtained are not right. Rational students are constrained on questions that are not routine but generally can solve all the questions well. Idealist student is constrained by non-routine questions, but in general, is able to solve problems with creative ideas.